Analisis Kesulitan Siswa Kelas XI Dalam Menyelesaikan Soal Fungsi Komposisi dan Fungsi Invers di SMK Al–Ikhsan Batujajar - Betha Susanti; Yuni Afriani Putri Lestari (Journal on Education, 2019)
This study aims to determine the difficulties of students in Vocational School in the material function of composition and inverse function. This research is a qualitative descriptive study, with a sample of students of class XI of Al-IHSAN Vocational School in Batujajar. Data analysis difficulties in solving questions obtained through tests, observations, and documentation. Validate data using triagulation methods. Data analysis techniques are carried out by the stage of data reduction, data recitation and conclusion drawing. The results of this study show the difficulties experienced by students in solving the problem of function composition and inverse functions include difficulties understanding concepts, difficulties in skills and difficulties in solving problems. The causal factor is that students do not understand the concept and have not been able to interpret the sentences, have not been able to understand the contents of the questions given, have not mastered the concept of using compositions, have not mastered the concept of inverse use, are not careful in working on the functions of composition and inverse functions.